1970
DOI: 10.1139/f70-110
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Carotenoids in Prespawning and Spawning Sockeye Salmon (Oncorhynchus nerka)

Abstract: Spawning sockeye salmon from the Wauk Wash River, B.C., contained 65% less carotenoid than prespawning fish taken at sea near Juneau, Alaska. Free astaxanthin in the muscle of spawning fish was only 1% of the amount noted for prespawning fish. Ninety-five percent of the pigment retained by the spawning males was located in the skin as esters and 85% of the pigment of spawning females was deposited in the eggs as free astaxanthin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
31
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 5 publications
9
31
1
Order By: Relevance
“…As is known, an intense red colour in fish is frequently due to the prevalence of astaxanthin, as has been found in Salmo salar specimens (Czeczuga, 1975), Oncorhyvnchus spp. (Kanemitsu & Aoe 1958;Crozier, 1970;Jarzombek, 1970;Czeczuga, 1979a). The red coloration of some parts of the body of fish may however result from the presence of another ketocarotenoid.…”
Section: Discussionmentioning
confidence: 99%
“…As is known, an intense red colour in fish is frequently due to the prevalence of astaxanthin, as has been found in Salmo salar specimens (Czeczuga, 1975), Oncorhyvnchus spp. (Kanemitsu & Aoe 1958;Crozier, 1970;Jarzombek, 1970;Czeczuga, 1979a). The red coloration of some parts of the body of fish may however result from the presence of another ketocarotenoid.…”
Section: Discussionmentioning
confidence: 99%
“…However, pigments in the muscles are not in sufficient quantity to provide all those deposited in ovaries and the fish must obtain them direct from natural food (Steven 1949). On the contrary, Crozier (1970) reported that muscle reserves were largely excedentary in sockeye salmon. In rainbow trout milt, Czeczuga (1979) also established the presence of carotenoid pigments but in low concentration.…”
Section: Essential Fatty Acids and Related Liposoluble Substancesmentioning
confidence: 97%
“…The accumulation of carotenoid pigments, mainly astaxanthin (Kitahara 1984), in gonads, ovules and eggs of salmonids is a well known phenomenon (Steven 1949;Crozier 1970). In brown trout, almost all muscle pigments are mobilized.…”
Section: Essential Fatty Acids and Related Liposoluble Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…No such reports have been published except for the studies by Crozier. 5 )He found that more than 60% of the carotenoids in sockeye salmon disappeared during spawning migration. This might suggest that carotenoids in fish are decomposed by some tissue, possibly the liver, during spawning migration.…”
mentioning
confidence: 99%